2011
DOI: 10.1016/j.jip.2011.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the reproductive biology of Biomphalaria glabrata experimentally infected with the nematode Angiostrongylus cantonensis

Abstract: This study showed for the first time changes in the reproductive biology of Biomphalaria glabrata experimentally infected with Angiostrongylus cantonensis. The values of all the parameters analyzed (total number of eggs, number of egg masses, number of eggs/mass, number of eggs/snail, percentage of viable eggs and galactogen content in albumen gland) changed with progressive infection. The results indicate the occurrence of partial parasitic castration of B. glabrata by A. cantonensis larvae, probably in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 11 publications
3
23
0
Order By: Relevance
“…also affect the snails through aminergic pathways as suggested by Delgado et al [34] and Vallejo et al [35]. For example, serotonin may be involved in parasitic castration [67], leading to a redirection of energy resources in infected snails [68][69][70][71][72]. Similarly, the presence of tyrosine hydroxylase-like immunoreactivity in the dorsal bodies of Biomphalaria [35] suggests that dopamine could also be involved in the diminished egg laying observed in infected snails [73].…”
Section: Discussionmentioning
confidence: 99%
“…also affect the snails through aminergic pathways as suggested by Delgado et al [34] and Vallejo et al [35]. For example, serotonin may be involved in parasitic castration [67], leading to a redirection of energy resources in infected snails [68][69][70][71][72]. Similarly, the presence of tyrosine hydroxylase-like immunoreactivity in the dorsal bodies of Biomphalaria [35] suggests that dopamine could also be involved in the diminished egg laying observed in infected snails [73].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that S. mansoni parasitism is able to suppress the production of eggs by the host snail. The process of partial or definitive reduction or interruption of fecundity is called parasitic castration, and two mechanisms have been postulated to explain its outcomes: a direct process related to parasite-induced snail tissue damage that destroys the hermaphrodite gland or an indirect process that is associated with decreased energy reserves (Baudoin, 1975;Thornhill et al, 1986;Thompson and Lee, 1986;Pan, 1965;Tunholi-Alves et al, 2011). The carbohydrate reserves in snails comprise two polysaccharides, glycogen and galactogen (Lustrino et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The nematode Angiostrongylus cantonensis and trematode parasites belonging to the genus Plagiorchis or Echinostoma are known to affect growth as well as fecundity and fertility of B . glabrata , and have thus been proposed as biological control agents [7476]. However, their use is not recommended since they may also cause severe human or animal infections.…”
Section: Discussionmentioning
confidence: 99%
“…A castration-like phenomenon similar to that observed in heavily infected snails has also been reported during parasitic infestation by S . mansoni [99,100], Plagiorchis elegans [74], and the nematode Angiostrongylus cantonensis [76]. This late infertility appears to be related to competition for energy resources between the host and pathogen [76,100].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation